Interfaith Communication on Social Media: Content Analysis Log In, Eps 30 “Tolerance, We Make History” - Hidayah, Childa Tanzilul (STAI AL-FALAH CICALENGKA, 2024)
This study examines the representation of interfaith communication in social media content through an analysis of the Log In program episode 30 entitled